An Investigation into the Relationship between Transformational Leadership Style and Organizational Commitment in a College of Administration and Economics: An Empirical Research - Fakhrulddin Mahmood*, Maryam (Journal of Economics and Administrative Sciences, 2024)
The current research aims to demonstrate the relationship and impact between transformational leadership and its dimensions (Idealized Influence Behaviour, Idealized Influence Attributed, Intellectual Stimulation, Inspiring Motivation, and Individual Consideration) on organizational commitment and its dimensions (continuous organizational commitment, emotional organizational commitment, and normative organizational commitment) at the College of Administration and Economics. Descriptive-analytical approach used to achieve the core object of the research. The research adopted the questionnaire as the core tool for this purpose. A research sample included various administrative levels (director, chief inspector, supervisor, and assistant supervisor). The questionnaire distributed randomly, and 70 valid questionnaires collected for statistical analysis. The research adapted a set of statistical methods such as arithmetic mean, coefficient of variation, standard deviation, and simple regression coefficient by the statistical program (SPSS V26) to analyze data and test hypotheses. The research reached a set of essential results, the most important of which was that transformational leadership is the main factor for building an organization’s culture to achieve growth and success and motivate individuals. Paper type: Research paper